Acute kidney injury 2016: diagnosis and diagnostic workup. Issue 1 (December 2016) - Ostermann, Marlies; Joannidis, Michael
Abstract Acute kidney injury (AKI) is common and is associated with serious short- and long-term complications. Early diagnosis and identification of the underlying aetiology are essential to guide management. In this review, we outline the current definition of AKI and the potential pitfalls, and summarise the existing and future tools to investigate AKI in critically ill patients.